(untitled) (Modern Problems of Metallurgy, 2024)
The uniqueness of ferroalloys from the point of view of their influence on the targeted formation of the desired structure and properties of metal melts is a rather scientific question that continues to be in trend for many years. Significant progress in the study of physicochemical and thermophysical characteristics of industrial ferroalloys has been achieved by both domestic and foreign scientists. At the same time, ferroalloys and their research have a number of difficulties caused by their high temperature and, as a result, the difficulties of conducting experiments from the standpoint of technological equipment limitations. It is these factors that significantly affect the availability of sometimes contradictory information in literary sources about the primary properties of ferroalloys and require their clarification. Given the demand for reliable data, the Institute of Ferrous Metallurgy is actively developing the Database System, which is a component of the "Metallurgy" data bank as an information foundation for modeling in smelting and blast furnace production. The purpose of the work is an expert assessment of the complex properties of domestically produced manganese-containing ferroalloys in order to obtain a competitive metal. One of the effective methods of describing the physical and chemical nature of the properties of metal melts and their numerical determination, explaining the processes of interactions between them is the concept of directed chemical bonding, which was founded by E.V. Prikhodko at the Iron and Steel Institute of Z.I. Nekrasov National Academy of Sciences of Ukraine. Based on its postulates, the main physicochemical properties of ferroalloys are considered: melting temperature, density, and thermophysical characteristics (thermal conductivity; heat capacity; heat of fusion; specific electrical resistance; temporary resistance). A statistical analysis of a representative sample of the chemical composition of industrial manganese-containing ferroalloys accumulated in the "Metallurgy" Data Bank was performed and analytical expressions for evaluating their physicochemical and thermophysical properties were proposed at the level of interatomic interaction. It is shown that the analysis of the chemical composition of the ferroalloy, only from the standpoint of compliance with the standards of the chemical composition, is not informative and insufficient for assessing the technological direction of its use. The presented complex of developed analytical expressions for predicting important physicochemical and thermophysical properties with high accuracy (R2≥0.9) will allow to create the principles of effective use of even a not quite functional (technological) ferroalloy in terms of its chemical composition. It is the assessment with a view to ensuring the required level of properties that provides reliable data for making management (rational technological) decisions for the production of competitive metal. The work shows that the use of domestic manganese-containing ferroalloys in the considered ranges of composition is possible according to their purpose, subject to certain conditions, according to an expert assessment based on the proposed models. Additional consideration and assessment of this issue made it possible to state the possibility of using domestic manganese-containing ferroalloys with the specified deviations in chemical composition in the production of mass steel.